Behavioral and biological risk factors of noncommunicable diseases among tribal adults of rural siliguri in Darjeeling District, West Bengal: A cross-sectional study - Ditipriya Bhar; Sharmistha Bhattacherjee; Dilip Kumar Das (Wolters Kluwer Medknow Publications, 2019)
Background: The increasing burden of noncommunicable diseases (NCDs) urges continuous survey of risk factors in different population groups. Objectives: The study was conducted to assess the prevalence and determinants of behavioral and biological risk factors of NCDs, in rural tribal population. Methods: A community-based cross-sectional study was conducted from June 2014 to May 2015, in rural Siliguri, among 172 tribal people aged 25-64 years selected by multistage cluster random sampling using WHO-STEPS instrument. Study participants were interviewed for sociodemographic and behavioral risk factors, and biological measurements were taken. Descriptive and logistic regression analyses were performed to explore the determinants of risk factors. Results: Among the study participants, the prevalence of current tobacco use and alcohol use were 69.8% and 40.7%, respectively; 96.5% consumed unhealthy diet and 2.9% were physically inactive. The prevalence of abdominal obesity and overweight were 26.2% and 12.2%, respectively. Odds of tobacco use were significantly raised among men (adjusted odds ratio [AOR]: 47.7 [95% confidence interval (CI) 11.1, 203.9]) and increased age of the participants. Men showed higher odds of alcohol consumption (AOR: 13.4 [95% CI 4.6, 38.9]). Odds of abdominal obesity were higher among older participants, whereas lower odds were found among men (AOR: 95% CI 0.11 [0.0, 0.5]) compared to women. Conclusions: Most of the behavioral and biological risk factors of NCDs were quite high among tribal population of rural Siliguri except physical inactivity. Increasing awareness about NCDs through locally accepted and culturally appropriate strategies need to be implemented in the study area.